A Characterization of Injuries Among Active Duty Personnel at Fort Riley, Kansas - Lopez, Tara C. (My University, 2012)
This report summarizes my experiences as a student extern at the Department of Public Health, Fort Riley, Kansas. This field experience was in partial fulfillment of the requirements of the Master of Public Health Program at Kansas State University. During the fall 2011 semester, I shadowed health department personnel, observed day-to-day operations, and assisted with various duties. During the student externship, I also conducted research under the direction of Lieutenant Colonel Paul Benne, Chief of Public Health at Fort Riley. Research was conducted on injuries among active duty personnel at Fort Riley. Injuries in the military are the greatest threat to combat readiness and the health of active duty personnel. Injuries related to physical activities and training are the primary reason service members seek medical treatment. This results in excessive limited duty days, high medical attrition rates, and tremendous health care costs for the military. Researchers have determined several risk factors, both intrinsic and extrinsic, that are associated with increased injury incidence. The purpose of the research at Fort Riley was to determine the incidence of injuries and musculoskeletal conditions among Army active duty personnel at Fort Riley, Kansas, between April 2010 and September 2011. Variables of interest included medical diagnosis, demographic data (age, gender, race), body mass index, unit, and disposition after injury (e.g., limited duty, hospitalization, etc.). Results showed that the leading injury diagnoses were musculoskeletal in nature and included low back pain and joint pain (primarily lower extremity). Injury rates were higher at Fort Riley than those that have been reported for the military as a whole. Recommendations to decrease injury rates at Fort Riley include continued, routine surveillance of injuries; education about appropriate prevention interventions; and adherence to policies and programs that are in place to prevent injuries.
Keywords: Fort Riley, Kansas; Injuries to Active Duty Personnel; Department of Public Health; Physical activity injuries; Limited duty days; Incidence of injiries; Public Health (0573)